Effect of spatial differentiation of plant communities on PM2.5 and O3 in urban green spaces in Beijing, China - Pan, Jianbin; Chen, Shuyu; Xu, Nuo; Cheng, Meijing; Wang, Xian; Lan, Jingwen; Wang, Rui; Wang, Yajie (Journal of Environmental Engineering and Landscape Management, 2024)
Urban green space can improve the air quality of urban human settlements. This study aimed to investigate the spatial differences of air quality among the different plant community structures and types of urban park green spaces. We select 17 sample sites in Beijing Olympic Forest Park, and they are located in different areas of plant community structures and types. The study entailed an analysis of the interrelationships between the plant community structures, types, and PM2.5, O3, and PM2.5–O3 compound data. The results showed that PM2.5 was lower in tree-shrub-grass, tree-shrub, and tree-grass than in shrub-grass and grass plant community areas; PM2.5 was lower in evergreen coniferous, mixed coniferous and broadleaved, and deciduous broadleaved plant communities than that in grass or shrub ones. In different plant community structures, types areas, O3 was higher than 100 μg·m–3, and there were no significant differences among the plant community areas. The air quality index with PM2.5–O3 composite pollution value as the main parameter reached the level of “moderate pollution”, and the result that deserves further attention. The research results provide a basic scientific basis for the planning, design, and updating optimization of functional urban green spaces based on evidence-based design.